PENGARUH PUPUK NPK DAN KASCING TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) FASE MAIN NURSERY - Manahan, Sabam '; ', Idwar '; ', Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to know the interaction between NPK fertilizer and vermicompost, as getting the best treatment on the growth of palm oil seedling main nursery phase. This research has been conducted in the experimental station of Agriculture Faculty, University of Riau in November 2015 to March 2016. The study was conducted by using factorial in completely randomized design (CRD), and two factors and three replications. The first factor is fertilizer NPK with 3 levels (0, 20 and 30 g / plant) and the second factor is vermicompost with 4 levels (0, 20, 40 and 60 g / plant). The parameters measured were the increase of plant height, the increase number of leaves, the increase of stem diameter, root volume, leaf area, plant N absortion and outbreak of the leaf. The results were analyzed statistically using analysis of varian (ANOVA) and followed by Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed that the interaction of NPK fertilizer and vermicompost provides no significant influence on the parameters the increase of plant height, the increase number of leaves, the increase of stem diameter leaf area but the interaction of NPK fertilizer and vermicompost provides significant influence on the parameters increase of root volume. Vermicompost application at a dose of 20 g / plant gives the highest N absortion. Â  Keyword: Vermicompost, NPK fertilizer and palm oil seedling